Body mass index and mortality among blacks and whites adults in the Prostate, Lung, Colorectal, and Ovarian (PLCO) Cancer Screening Trial. (2nd July 2013) - Xiao, Qian; Hsing, Ann W.; Park, Yikyung; Moore, Steven C.; Matthews, Charles E.; Berrington de González, Amy; Kitahara, Cari M.
Abstract : Objective: In a large prospective cohort, we examined the relationship of body mass index (BMI) with mortality among blacks and compared the results to those among whites in this population. Design and Methods: The study population consisted of 7, 446 non‐Hispanic black and 130, 598 white participants, ages 49‐78 at enrollment, in the Prostate, Lung, Colorectal and Ovarian (PLCO) Cancer Screening Trial. BMI at baseline, BMI at age 20, and BMI change were calculated using self‐reported and recalled height and weight. Relative risks were stratified by race and sex and adjusted for age, education, marital status, and smoking. Results: During follow‐up, 1, 495 black and 18, 236 white participants died (mean = 13 years). Clear J‐shaped associations between BMI and mortality were observed among white men and women. Among black men and women, the bottoms of these curves were flatter, and increasing risks of death with greater BMI were observed only at higher BMI levels (≥35.0). Associations for BMI at age 20 and BMI change also appeared to be stronger in magnitude in whites versus blacks, and these racial differences appeared to be more pronounced among women. Conclusion: Our results suggest that BMI may be more weakly associated with mortality in blacks, particularly black women, than in whites.